Stock Prices and Exchange Rates under Monetary Policy Changes: The Cases of Japan and the US - Kurihara, Yutaka; Maeda, Shinichiro; Fukushima, Akio (Archives of Business Research, 2024)
This study examines exchange rates and stock prices in the context of US and Japanese monetary policy shifts. Also, the effects of announcements made by the monetary authorities are examined. The empirical results show that US stock prices have positive impacts on Japanese stock prices. As predicted, there is a negative correlation between Japanese interest rates and stock prices. Depreciation of the Japanese yen leads to rising stock prices. Although the Bank of Japan’s announcement of “positive” news that the end of quantitative easing is expected to cause stock prices to decline, they instead increased. In the case of the US, however, appreciation of the US dollar promotes rising stock prices. This result is the opposite of the Japanese case. It may be concluded that there exists good communication between the monetary authorities and the markets, and that the news causes no unexpected effects or confusion on the financial markets.